The Effect of Skipping Exercises in Increasing Cardiovascular Endurance of Running Athletes in Bone Bolango Regency - Hunta, Mohamad Akil; Duhe, Edy Dharma Putra; Haryanto, Arief Ibnu (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2025)
This study aims to analyze the effect of skipping exercises on improving cardiovascular endurance among running athletes in Bone Bolango Regency. The research employs a quasi-experimental design with a pretest-posttest approach. The study involved nine athletic athletes as participants, who were subjected to skipping exercises over a specified training period. The cardiovascular endurance of the athletes was measured using the Bleep Test before and after the intervention. Data analysis included normality tests, homogeneity tests, and t-tests to determine the statistical significance of the results. The findings indicate a significant improvement in the athletes' cardiovascular endurance, as demonstrated by increased VO₂ max values after the skipping exercise program. The t-test results showed that skipping exercises have a statistically significant impact on cardiovascular endurance (Tcount = 23.263 Ttable = 2.306, P-Value = 0.00 0.05). These results suggest that skipping exercises can serve as an effective and practical training method to enhance cardiovascular endurance in running athletes.